Improvement of piezoelectricity of (Na, K)Nb-based lead-free piezoceramics using [001]-texturing for piezoelectric energy harvesters and actuators. Issue 14 (November 2022) - Go, Su-Hwan; Kim, Hero; Kim, Dae-Su; Eum, Jae-Min; Chae, Seok-June; Kim, Eun-Ji; Nahm, Sahn
Abstract: 0.96(Na0.5 K0.5 )(Nb0.93 Sb0.07 )O3 −(0.04−x)BaZrO3 −x(Bi0.5 Ag0.5 )ZrO3 [NKNS−(0.04−x)BZ−xBAZ] ceramics are well textured along the [001] direction using 3.0 mol% NaNbO3 seeds. The textured-NKNS−0.02BZ−0.02BAZ thick film has a rhombohedral-orthorhombic-tetragonal (R-O-T) structure with a large proportion of the O-R structure (> 80%). This specimen exhibits the largest values for d 33 (805 pC/N) and d 33 × g 33 (29.5 ×10 −12 m 2 /N), which are the largest d 33 and d 33 × g 33 values of NKN-based piezoceramics to date. It exhibits a large strain (0.17% at 4.0 kV/mm). Therefore, it is an outstanding piezoceramic material for piezoelectric energy harvesters (PEHs) and actuators. A PEH and actuator are fabricated using this specimen. The PEH shows a large power density (4.3 mW/cm 3 ), which is the largest value among the PEHs produced by lead-free piezoceramics. The actuator exhibits a large acceleration (50.8 G) and displacement (3.9 mm), which are the best actuating properties among the actuators produced by lead-free piezoceramics. Therefore, texturing is an excellent technique for improving the piezoelectricity of NKN-based piezoceramics. Highlights: Textured NKNS-0.02BZ-0.02BAZ has an R-O-T structure with a large fraction of R-O. This sample shows the largest d 33 (805 pC/N) among the NKN-based piezoceramics. A PEH fabricated using this specimen shows a large output power density (4.3 mW/cm 3 ). An actuator produced using this specimen exhibits excellent actuating properties. Texturing is a good method for improving the piezoelectricity of NKN-based ceramics.